2013
DOI: 10.1038/bmt.2013.191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two different doses of antithymocyte globulin in patients with standard-risk disease following haploidentical transplantation: a randomized trial

Abstract: To evaluate the effect of the different doses of antithymocyte globulin (ATG) on the incidence of acute GVHD among patients receiving hematopoietic SCT without ex vivo T-cell-depletion from haploidentical donors, 224 patients with standard-risk hematological malignancy were randomized in this study. One hundred and twelve patients received 6 mg/kg ATG, whereas the remaining patients received 10 mg/kg ATG. This study was registered at http://www.chictr.org as No. ChiCTR-TRC-11001761. The incidence of grade III-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 24 publications
7
134
0
Order By: Relevance
“…7,10,12,13 In our study, we found that lower dose ATG-F decreased the incidence of cGvHD without influencing aGvHD. Similar results have been reported by Bonifazi et al…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…7,10,12,13 In our study, we found that lower dose ATG-F decreased the incidence of cGvHD without influencing aGvHD. Similar results have been reported by Bonifazi et al…”
Section: Discussionmentioning
confidence: 59%
“…However, with the exception of one study with matched-related HSCT only, 21 these studies did not reach statistical significance. [7][8][9][10]13,22 The survival benefit shown here may be due to an improved selection of patients receiving ATG. Although the imbalance of known risk factors was adjusted for by statistical analysis, larger series of patients need to be analyzed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,36,37 aGVHD was defined and graded from 0 to 4 based on the Seattle criteria. 38 cGVHD was defined and graded according to the NIH criteria.…”
Section: Definitions and Evaluationmentioning
confidence: 99%